The paths of epistolary genre: history and critical fortune of the correspondence of Baudelaire - Abes, Gilles Jean (Lettres Françaises, 2016)
This article aims at presenting the specificities of the epistolary genre, as well as different perspectives of approach in the letters of authors, artists or musicians. Subsequently, we describe the journey of the publication of the letters of the poet Charles Baudelaire, tracing the history of his missives, whose richness, still little explored, is of great value to researchers.